The Inclusion of a Supercritical Fluid Extract, Obtained From Honey Bee Pollen, in the Diet of Gilthead Sea Bream (Sparus aurata), Improves Fish Immune Response by Enhancing Anti-oxidant, and Anti-bacterial Activities - Messina, Concetta Maria; Panettieri, Valentina; Arena, Rosaria; Renda, Giuseppe; Espinosa Ruiz, Cristobal; Morghese, Maria; Piccolo, Giovanni; Santulli, Andrea; Bovera, Fulvia (Frontiers in Veterinary Science, 2020)
In the present study, the immune-stimulatory effect of two levels of honey bee pollen (5% and 10%, P5 and P10 treatment respectively) and its supercritical fluid extract (0.5% and 1%, E0.5 and E1 respectively) included in the diet, was tested in gilthead seabream (Sparus aurata). The in vivo trial was preceded by the evaluation of antioxidant properties of three different bee pollen extracts obtained by water, ethanol 80% and Supercritic Fluids Extraction (SFE). The preliminary evaluation attested that the SFE showed the lowest extraction yield (10.47%) compared to ethanol 80% (48.61%) and water (45.99%). SFE extract showed good antioxidant properties with high polyphenol content (13.06mg GAE/g), radical scavenging activity (3.12mg/ml), reducing power (38.68 mg/mL EC50), On the contrary, the water extract showed the significantly lowest polyphenol content (2mg GAE/g; P<0.05). The results of in vivo trial demonstrate that the diets supplemented with SFE bee pollen extract had a stimulatory effect on fish serum immunity, respect to the inclusion of raw pollen, this latter revealing some inhibitory effects in the immune response, such a decrease of serum peroxidase and lysozyme activities, particularly in P10 group significantly different (P<0.05) from the control group. On the contrary, serum peroxidase, protease, antiprotease, were significantly increased in fish fed the diets supplemented with supercritical fluid extract, respect to the fish fed on control and on diets supplemented with 5% and 10% of raw pollen. For what concerns the bactericidal activity against Vibrio harveyii, all the treatments containing bee pollen regardless of the type showed their serum bactericidal activity significantly increased with respect to the control groups (p<0.05). Given its high antioxidant properties, the absence of toxic solvents and the positive action carried out on improving the humoral response in gilthead seam bream, honey bee pollen SFE extract can be taken into account in the formulation of fish feeds.